KEMAMPUAN MENULIS汉字 (Hànzì) SISWA KELAS XII SMA INSAN CENDEKIA SYECH YUSUF GOWA - Ainun Bashirah Syam; Ambo Dalle; Arini Junaeny (Universitas Negeri Makassar, 2020)
Abstract. This research is a descriptive quantitative research that was aimed to determine the ability and factors influencing the 12th grade students of SMA Insan Cendekia Syech Yusuf in writing汉字 [Hànzi]. The population in this study is 23 students from class XII MIA 2 SMA Insan Cendekia Syech Yusuf. The total of sample consisted of 10 students who were obtained purposively (purposive sampling). The data of this study were obtained through the 汉字 [Hànzi] writing test and questionnaires. The test results showed an average value of 48.8% and was in the very poor category. From the results of the questionnaire distribution, it was found that there are two factors that play an important role in influencing the students' ability of writing 汉字 [Hànzi], which are: 1) Supporting factors such as teacher's interesting way of teaching Chinese that make the students' interest in learning Mandarin is very high. 2) The inhibiting factors such as: Mandarin is a difficult subject; students do not know the basic rules in writing 汉字[Hànzi]; the lack of writing practice outside and inside class hours; difficulty in remembering Hanzi characters; parents rarely provide motivation to learn Mandarin